Inner ear fluid‐attenuated inversion recovery MRI signal intensity in dogs with vestibular disease. Issue 5 (20th June 2020) - Castillo, Gibrann; Parmentier, Thomas; Monteith, Gabrielle; Gaitero, Luis
Abstract: The inner ear contains endolymph and perilymph. The second is comparable and in continuity with the cerebrospinal fluid (CSF) so it is expected to suppress in fluid‐attenuated inversion recovery (FLAIR) magnetic resonance imaging (MRI) if normal. Even though inner ear FLAIR abnormalities have been extensively described in humans with inner ear disease, its diagnostic value in dogs is yet to be proven. The goal of this retrospective cohort study was to investigate the diagnostic utility of FLAIR MRI in dogs with vestibular disease. A review of medical records identified 101 dogs that had brain MRI performed because of vestibular signs. Based on the final diagnosis, patients were allocated to three groups: otitis media/interna, idiopathic vestibular disease, and central vestibular disease. Additionally, a control group (n = 73) included dogs with normal MRI and without vestibular signs. Inner ears were delineated using a region of interest, and signal intensity was measured in FLAIR and T2‐weighted images. The percentages of suppression in FLAIR were calculated and compared between affected and unaffected sides of each individual and between groups using a general linear mixed model. Correlation between suppression and CSF cell count and protein concentration was assessed. Affected inner ears in dogs with otitis media/interna had decreased suppression in FLAIR compared to the unaffected side ( P  < .001), and all other groups ( P  < .01). No significant correlation was detected between CSF results and suppression. These results show the diagnostic value of FLAIR in otitis media/interna due to lack of suppression in the affected inner ear.